Characterization of a pH-dependent chromophore from nutritionally variant streptococci. - van de Rijn, I (1984)
Strains of nutritionally variant streptococci and Streptococcus mitis produce a chromophore when they are heated at acid pH. No other strains of streptococci elaborated this chromophore. Furthermore, the nutritionally variant streptococci produced approximately twice the amount of chromophore as the S. mitis strains. The chromophore was localized in the cell wall of these streptococcal strains and appeared to be resistant to trypsin treatment. Hydrolysis apparently is required because elevated temperatures at pH 2 are necessary for demonstration of the chromophore. The chromophore has a maximal absorbance at 504 nm with a pKa of 3.6. The chromophore absorbance spectrum showed an isosbestic point at 400 nm. This is the first example of a pH-dependent chromophore to be found in streptococci and serves as a positive characteristic for the description of nutritionally variant streptococci as well as S. mitis.